Np(V) complexation with propionate in 0.5-4 M NaCl solutions at 20-85 °C - Vasilʹev, Aleksandr Aleksandrovič; Banik, Nidhu Lal; Marsac, Rémi; Fröhlich, Daniel R.; Rothe, Jörg; Kalmykov, Stepan N.; Marquardt, Christian (Dalton transactions, 2015)
Low molecular weight organics (LMWO; e.g. acetate, propionate, lactate) can significantly impact the speciation and mobility of radionuclides in aqueous media. Natural clay rock formation, considered as a potential host rock for nuclear waste disposal, can contain a significant amount of organic matter. There are less thermodynamic data reported for the complexation of pentavalent actinides with LMWO, especially under elevated temperature conditions, relevant for assessing the long-term safety of disposal options for heat-producing high-level nuclear waste. In the present study, the complexation of Np(V) with propionate is studied using spectroscopic techniques in 0.5-4 M NaCl solutions by systematic variation of the ligand concentration and temperature. Slope analysis shows the formation of the 1 : 1 NpO2-propionate complex (NpO2Prop). The local structure of the NpO2-propionate complex is determined by extended X-ray absorption fine structure spectroscopy, the results of which suggest that propionate binds to Np(V) in a bidentate mode. Using the specific ion interaction theory (SIT), the stability constant at zero ionic strength and 25 °C is determined as log β°1,1 = 1.26 ± 0.03. The stability constants increase continuously with increasing temperature between 20 and 85 °C. The log β0 values are linearly correlated with the reciprocal temperature, indicating ΔrH0m = const. and ΔrC0p,m = 0, allowing the calculation of ΔrH0m and ΔrS0m for the formation of the NpO2-propionate complex using the integrated van't Hoff equation. The thermodynamic evaluation indicates that the reaction is endothermic and entropy driven.